(untitled) (Journal of Naval Architecture and Marine Engineering, 2023)
In this study, the implicit Finite Volume Method (FVM) based on Reynolds-Averaged Navier-Stokes (RANS) equations are used to simulate the flow past a hydrofoil that is submerged in the vicinity of the free surface of water. To simulate the turbulent flow around the hydrofoil surface, realizable k-ε turbulence model is used. The Volume of Fluid (VOF) method is incorporated into the numerical simulation to capture the interface between water and air. The free surface wave generated by the stream around NACA 0012 hydrofoil is computed and compared with experimental results to validate the numerical simulation. Grid independency is checked by using three different grid sizes and the validation is done by comparing the experimental results of ratio of submergence level h/c=0.95. Finally, the cambered hydrofoil NACA 2412 is analyzed to predict the free surface water waves for seven submergence ratios, ranging from submergence level h/c= 0.95 to 5.5. The pressure coefficient, velocity contour, static pressure contour, and force coefficients are shown graphically and in tabular form for Froude number 0.57. The restricted and shallow water effects are also studied in this research. This study reveals that implicit finite volume method can predict the wave of free surface due to flow past cambered hydrofoil satisfactorily. J. Nav. Arch. Mar. Engg., Vol 20(2), December, 2023; p 1-10